2015
DOI: 10.1111/sms.12530
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of individual adaptation to high‐volume or high‐intensity endurance training in recreational endurance runners

Abstract: The aim of this study was to investigate factors that can predict individual adaptation to high-volume or high-intensity endurance training. After the first 8-week preparation period, 37 recreational endurance runners were matched into the high-volume training group (HVT) and high-intensity training group (HIT). During the next 8-week training period, HVT increased their running training volume and HIT increased training intensity. Endurance performance characteristics, heart rate variability (HRV), and serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
4
33
1
Order By: Relevance
“…This finding is consistent with other recent studies (16,34). Furthermore, a response distribution analysis for Power 40min revealed no significant differences in the variability of response across groups (Fig.…”
Section: Individual Differences In Adaptations Responsesupporting
confidence: 93%
“…This finding is consistent with other recent studies (16,34). Furthermore, a response distribution analysis for Power 40min revealed no significant differences in the variability of response across groups (Fig.…”
Section: Individual Differences In Adaptations Responsesupporting
confidence: 93%
“…Patil et al (2013) reported that yoga practice helped to reduce mental stress associated with chronic training in cyclists and optimized autonomic cardiac function. In addition to the above factors, attenuated vagal activity is related to intensive blocks of training (Pichot et al, 2000) and is significantly associated with weaker adaptation responses to both aerobic (Botek et al, 2014a; Buchheit, 2014; Hautala et al, 2009; Vesterinen et al, 2015) and anaerobic training (Boutcher et al, 2013). Based on our findings, we propose the implementation of regular HRV monitoring during training in professional soccer players as it provides important diagnostic information about changes in autonomic cardiac regulation over their careers.…”
Section: Discussionmentioning
confidence: 99%
“…We expected a significant increase of this marker between T0 and T1, i.e., between the end of a period of inactivity and the end of a gradual resumption of soccer ("Warmup" period, Carter et al 2003;Mourot et al 2004a;Buchheit et al 2010;Vesterinen et al 2015). Professional soccer players are highly trained and the period of inactivity was perhaps not long enough to detrain them significantly.…”
Section: Hrv In the Supine Positionmentioning
confidence: 97%
“…The lack of significant change in lnRMSSD in the supine position during this training period could be a consequence of heterogeneity induced in our study group by the training itself. All the players followed the same training programme while it is known that their positions (striker or side defender) alter training load on the first hand (Ingebrigtsen et al 2015) and that training adaptation depend upon individuals on the second hand (Vesterinen et al 2015). Moreover, several patterns of fatigue have been described including by means of HRV (Schmitt et al 2015).…”
Section: Hrv In the Supine Positionmentioning
confidence: 99%